Regulation of Customary Villages as Legal Subjects and Appointment of Temples as Religious Legal Entities Related to Land Ownership Rights - I Nyoman Sumardika; I Nyoman Sutama (Community Service Journal of Law, 2025)
This study analyzes the legal position of temples (pura) as religious legal entities in the context of land registration following the enactment of Bali Provincial Regulation Number 4 of 2019 on Desa Adat (Customary Villages). The regulation introduces new classifications of legal subjects eligible for land registration, particularly concerning land owned by Desa Adat and temple property. These developments raise two fundamental legal questions: (1) whether temple-owned land can be categorized as land belonging to the Desa Adat, and (2) the legal basis for registering temple land under the 2019 regulation. The research adopts normative legal methods, relying on statutory, conceptual, and case approaches to clarify the legal norms relevant to temple land registration. Analysis is conducted through grammatical and systematic interpretation, enabling a structured understanding of the regulatory framework. Desa Adat is formally recognized as a holder of communal land rights under the Decree of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 276/KEP-19.2/X/2017, a status further supported by Bali Provincial Regulation Number 4 of 2019. Two forms of customary village land eligible for registration are identified: (a) land directly managed by the Desa Adat, including cemeteries, certain temple areas, and markets; and (b) land owned by the Desa Adat but managed by customary community members, such as village yards and ayahan land. The function of Desa Adat in customary land registration does not conflict with the Minister of Home Affairs Decree Number 556/DJA/1986, which is based on Government Regulation Number 38 of 1963 regarding legal entities permitted to hold land ownership rights. Nonetheless, these regulations differ substantially in scope and purpose. The key finding of this study is that temple land remains legally distinct from customary village land, as temples and Desa Adat constitute separate legal entities. Consequently, temple-owned land cannot automatically be treated as Desa Adat property, and its registration must follow legal provisions specific to temples as religious legal bodies.